ANALISIS EFESIENSI BELANJA MODAL PADA DINAS PEKERJAAN UMUM DAN PENATAAN RUANG KOTA PAREPARE - Nuryadin, Rusmin (Universitas Muhammadiyah Parepare, 2019)
This study aims to determine the efficiency of capital expenditure in 2013-2017. The data collection techniques used in this study are observation, interview, and documentation. Data analysis techniques in this study use efficiency efficiency ratio formula. Capital Expenditures are regional government expenditures whose benefits exceed one fiscal year and will increase regional assets or wealth and subsequently will add routine expenditure such as maintenance costs to general administration expenditure groups according to PP No. 71 of 2010. The results of the study that Capital Expenditures from 2013-2017 have been in efficient criteria. Where in 2013 it was categorized as efficient, in 2014, 2016, 2017 was categorized as quite efficient, and in 2015 it was categorized as very efficient.